An Update on WHO Classification of Thoracic Tumours 2021- Newly Described Entities and Terminologies - Gyanendra Singh; Anurag Singh; Rushang Dave (Journal of Clinical and Diagnostic Research, 2023)
The 5th edition of the World Health Organisation (WHO) “Classification of Thoracic Tumours” replaces the previous edition from 2015, which was released in 2021. The new edition includes specific diagnostic criteria for each entity and lays a stronger emphasis on diagnostic molecular pathology. Immunohistochemistry (IHC) was heavily promoted in 2015, as a way to improve classification precision. The book places more attention on molecular pathology developments for all tumour types in 2021. Classification based on microscopic biopsy samples of the characteristics of lung cancer is an alternative to resection-based categorisation. A grading system for invasive non mucinous adenocarcinomas has been developed, using the percentage of distinctive histological patterns found inside each tumour. Lung adenocarcinoma is also predisposed by Tumour Spread Through Air Spaces (STAS). A basaloid variety of Squamous Cell Carcinoma (SCC) and lymphoepithelial carcinoma was added to the SCC group. The ciliated muconodular papillary tumour and thoracic SMARCA4-deficient undifferentiated carcinoma are recent inclusions. Therefore, the following new terms and entities have been added to the WHO classification of 2021: (1) Thoracic SWI/SNF related, matrix associated, actin dependent regulator of chromatin, subfamily a, member 4 (SMARCA4)-deficient undifferentiated tumour; (2) Bronchiolar adenoma/ciliated muconodular papillary tumour; (3) Primary pulmonary hyalinising clear cell carcinoma of lung; (4) Lypmphoepithelial carcinoma; (5) STAS.